Properties of Polyurethane Foam/Coconut Coir Fiber as a Core Material and as a Sandwich Composites Component - M. A., Azmi; H. Z., Abdullah; M. I., Idris (2013)
This research focuses on the fabrication and characterization of the sandwich composites panel using glass fiber composite skin and polyurethane foam reinforced coconut coir fiber core. The main objectives are to characterize the physical and mechanical properties and to elucidate the effect of coconut coir fibers in polyurethane foam cores and sandwich composites panel. Coconut coir fibers were used as reinforcement in polyurethane foams in which later were applied as the core in sandwich composites ranged from 5 wt% to 20 wt%. The physical and mechanical properties found to be significant at 5 wt% coconut coir fiber in polyurethane foam cores as well as in sandwich composites. It was found that composites properties serve better in sandwich composites construction.